2018
DOI: 10.3103/s0027134918020030
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Variations in the Solar Radiation Fluxes at the Beginning of the 21st Century

Abstract: The solar activity in the current, that is, the 24-th, sunspot cycle is analyzed. Cyclic variations in the sunspot number (SSN) and radiation fluxes in various spectral ranges have been estimated in comparison with the general level of the solar radiation, which is traditionally determined by the radio emission flux F 10.7 at a wavelength of 10.7 cm (2.8 GHz). The comparative analysis of the variations in the solar constant and solar indices in the UV range, which are important for modeling the state of the Ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…A comparative analysis of several solar activity indices in cycles 22,23 and 24 showed that the relative differences in the amplitudes of variations of activity indices from the minimum to the maximum of the cycle vary significantly during the transition from cycles 22 and 23 to cycle 24. But, the maximum amplitudes of variations of the flare index FI, of the relative number of sunspots SSN and of the UV flux in the hydrogen line 121.6 nm F Lα are significantly decreased (by 20 -50%) already in cycle 23 compared to cycle 22. Amplitudes of variations of the MgII index 280 nm (center/wings), of radio emission flux on the 10.7 cm F 10.7 , of the background flux in the Soft Xray range and of the solar constant TSI decreased by 20-30%, and variations of SSN and of FI decreased by 30 -50% in cycle 24 compared to cycle 23, [4].…”
Section: Introductionmentioning
confidence: 93%
“…A comparative analysis of several solar activity indices in cycles 22,23 and 24 showed that the relative differences in the amplitudes of variations of activity indices from the minimum to the maximum of the cycle vary significantly during the transition from cycles 22 and 23 to cycle 24. But, the maximum amplitudes of variations of the flare index FI, of the relative number of sunspots SSN and of the UV flux in the hydrogen line 121.6 nm F Lα are significantly decreased (by 20 -50%) already in cycle 23 compared to cycle 22. Amplitudes of variations of the MgII index 280 nm (center/wings), of radio emission flux on the 10.7 cm F 10.7 , of the background flux in the Soft Xray range and of the solar constant TSI decreased by 20-30%, and variations of SSN and of FI decreased by 30 -50% in cycle 24 compared to cycle 23, [4].…”
Section: Introductionmentioning
confidence: 93%
“…5. It has been observed [45] that "the pre-flare enhancement propagates from the higher levels of the corona into the lower corona and chromosphere." It is perfectly consistent with our proposal as the dark matter AQNs enter the solar atmosphere from outer space.…”
Section: Aqns As the Corona's Heatersmentioning
confidence: 99%
“…Благодаря локальному характеру материнского вейвлета, вейвлет-преобразование позволяет эффективно выявлять параметры нестационарных вариаций. В [3], при анализе вейвлета Морли рядов различных индексов СА, на масштабе периодов 1-3.5 года была отмечена тенденция появления последовательностей уменьшающихся периодов. В данной работе мы использовали вейвлет-преобразование с материнским вейвлетом Добеши (Daubechies)10, который позволяет наиболее наглядно выявлять линейный тренд и эффективно отфильтровывать шумы.…”
Section: Doi: 1031725/0552-5829-2018-243-246unclassified